Quality assessment of heat-treated wood by NIR spectroscopy - Esteves, Bruno (2021)
NIR spectroscopy was tested for predicting the properties of heat treated wood using pine (Pinus pinaster) and eucalypt (Eucalyptus globulus) woods with two types of treatment: in oven and in a steam autoclave. Mass loss, equilibrium moisture content, dimensional stability, MOE, bending strength, colour CIELAB parameters and extrac- tives content were determined. NIR spectra were obtained using a fibre probe on the radial surface of the samples. NIR models for mass loss showed very high coefficients of determination ( R2 ) for cross validation ranging from 96– 98%. The models obtained for wood properties were in gen- eral good with coefficients of determination ranging from 78–95% for equilibrium moisture content, 53–78% for di- mensional stability, 47–89% for MOE, 75–77% for bending strength and 84–99%, 52–96% and 66–98% for colour pa- rameters L, a∗ and b∗, respectively. R2 of the models for extractive content varied between 41.9–79.8% for pine and between 35.3–82.2% for eucalypt wood. NIR spectroscopy showed a good potential for quality control and characteri- zation of heat treated woods.